Application of High-Voltage Discharges for Disinfecting Water - Alexander Anatolievich Belov; Alexey Nikolayevich Vasilyev (IAES Indonesian Section, 2020)
A three-factor experiment is conducted on the disinfection of water by treatment with high-voltage discharges formed to achieve an electro-hydraulic effect, in order to detect optimal conditions and rules for the course of the processes under study. In the study, a high-voltage installation with an electro-hydraulic spark gap, an EnSURE luminometer (Hygiena) for measuring the level of hygiene of water and its solutions, test tubes for determining the total number of ATP in AquaSnap Total brand water (AQ100X) are used as materials and equipment. The influence of design parameters and exposure modes of an electro-hydraulic installation on the properties of water as a result of the generation of high-voltage discharges is investigated; experimental data are revealed for measuring the level of microbiological contamination of the water sample, which, according to the analysis of the data obtained, is reduced, which can serve as the basis for the possibility of the potential use of the effects of high-voltage discharges as a method of preparing water under irrigation in greenhouses; optimal ratios of factors for disinfecting a pond water sample from a source of artificial origin are revealed: operating voltage 19.9 kV, capacitance 0.1445 μF and the number of discharges 2861 pieces.